2023
DOI: 10.3389/fimmu.2022.1054273
|View full text |Cite
|
Sign up to set email alerts
|

Safety of COVID-19 vaccination in women undergoing IVF/ICSI treatment - Clinical study and systematic review

Abstract: BackgroundIt was suggested that vaccination in general might affect reproductive health. Safety of COVID-19 vaccination in women undergoing assisted reproductive techniques (ART) treatment is not well established.MethodsWe performed a retrospective study including 536 women undergoing fresh embryo transfer after IVF/ICSI treatment in a huge IVF center in southern China to investigate the effect of COVID-19 vaccination on oocyte maturation, fertilization rate, blastulation rate, implantation rate, clinical preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“…We also analyzed data on whether COVID-19 vaccines affected the number of oocytes and MII/mature oocytes, blastocysts rate, and fertilization rate. Data on the number of oocytes from nine studies ( 18 , 19 , 22 , 24 28 , 33 ) were combined, and the difference was not statistically significant (MD: 0.12; 95% CI: −0.65–0.88; P = 0.77; Figure 6 ). Moreover, there was no statistically significant difference in the number of MII/mature oocytes between the vaccinated and unvaccinated groups from seven studies (MD: 0.27; 95% CI: −0.36–0.90; P = 0.40; Figure 7 ) ( 18 20 , 25 , 26 , 28 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We also analyzed data on whether COVID-19 vaccines affected the number of oocytes and MII/mature oocytes, blastocysts rate, and fertilization rate. Data on the number of oocytes from nine studies ( 18 , 19 , 22 , 24 28 , 33 ) were combined, and the difference was not statistically significant (MD: 0.12; 95% CI: −0.65–0.88; P = 0.77; Figure 6 ). Moreover, there was no statistically significant difference in the number of MII/mature oocytes between the vaccinated and unvaccinated groups from seven studies (MD: 0.27; 95% CI: −0.36–0.90; P = 0.40; Figure 7 ) ( 18 20 , 25 , 26 , 28 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Data on the number of oocytes from nine studies ( 18 , 19 , 22 , 24 28 , 33 ) were combined, and the difference was not statistically significant (MD: 0.12; 95% CI: −0.65–0.88; P = 0.77; Figure 6 ). Moreover, there was no statistically significant difference in the number of MII/mature oocytes between the vaccinated and unvaccinated groups from seven studies (MD: 0.27; 95% CI: −0.36–0.90; P = 0.40; Figure 7 ) ( 18 20 , 25 , 26 , 28 , 33 ). The rates of blastocyst formation ( 20 , 24 27 , 33 ) and fertilization ( 20 , 22 , 24 27 ) were also not significantly different between the vaccinated and unvaccinated groups (MD: 0.01 vs. 1.08; 95% CI: −0.04–0.06 vs. −0.57–2.73; P = 0.70 vs. P = 0.20, respectively; Figures 8 , 9 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most data derive from mRNA vaccines, and data from early reproductive and toxicity studies have reported similar efficacy and safety [ 75 , 76 , 77 ]. Rare side effects include thrombosis with thrombocytopenia syndrome, myocarditis, and pericarditis, Guillain–Barré syndrome, as in nonpregnant individuals; however, no infertility issues have been reported [ 78 , 79 , 80 , 81 ]. Pregnancy by itself does not represent a cause for increased risks of any adverse outcome, following COVID-19 vaccination [ 82 ], while the overall risk of the occurrence of an acute adverse event requiring medical attention is low (<1%) and similar in pregnant and unvaccinated pregnant patients [ 83 ].…”
Section: Discussionmentioning
confidence: 99%